A novel method of biopsy for indeterminate pancreaticobiliary strictures: tube-assisted biopsy - Ko, Sung Woo; Lee, Sang Soo; So, Hoonsub; Hwang, Jun Seong; Song, Tae Jun; Lee, Sung Koo; Kim, Myung-Hwan (Endoscopy, 2020)
Background Single-operator cholangioscopy (SOC) provides an accurate diagnosis of indeterminate pancreaticobiliary strictures. However, the procedure is expensive and can be performed using only limited accessories. Therefore, we devised a novel tube-assisted biopsy (TAB) technique and evaluated its feasibility, diagnostic yield, and safety for indeterminate pancreaticobiliary strictures.Methods The medical records of patients with indeterminate pancreaticobiliary strictures who underwent TAB between September 2018 and July 2019 were reviewed. We assessed the technical success rate, adverse event rate, sensitivity, specificity, and overall accuracy of TAB in differentiating malignant from benign lesions.Results TABs were performed in 16 patients: 12 had biliary strictures; four had pancreatic strictures. The technical success rate was 93.7 % (15/16), and the sensitivity, specificity, and overall accuracy of TAB were 87.5 %, 100 %, and 93.7 %, respectively. No serious adverse events occurred either during or after the procedure in any of the patients.Conclusions TAB has an acceptable accuracy for the diagnosis of indeterminate pancreaticobiliary strictures and may represent a useful diagnostic method in patients where SOC cannot be implemented.